Attribute framing affects the perceived fairness of health care allocation principles - Eyal Gamliel; Eyal Peer (Judgment and Decision Making, 2010)
Health care resource allocation is a central moral issue in health policy, and opinions about it have been studied extensively. Allocation situations have typically been described and presented in a positive manner (i.e., who should receive medical aid). On the other hand, the negative valence allocation situation (i.e., who should not receive medical aid) has been relatively neglected. This paper demonstrates how positive versus negative framing of the exact same health care resource allocation situation can affect the perceived fairness of allocation principles. Participants usually perceived non-egalitarian principles (i.e., need, equity and tenure) to be fairer in positively framed situations (i.e., to deliver health care resources to certain patients) than negatively framed situation (i.e., not to deliver health care resources to other patients). However, framing did not affect the perceived fairness of the equality principle (i.e., a random draw). The paper offers a theoretical explanation for the effect of framing on the perceived fairness of health care resource allocation and discusses implications for both researchers and policy makers.